Marshall and Friedman on Union Strength - Ulman, Lloyd (The Review of Economics and Statistics, 1955)
IN a recent essay Professor Milton Friedman claimed that . . laymen and economists alike tend . . . to exaggerate greatly the extent to which labor unions affect the structure and level of wages. ' His estimate is that not over Io per cent and certainly not over 20 per cent of the labor force can be supposed to have had their wages significantly affected by the existence of unions. 2 This interesting conclusion is held to flow from a theoretical analysis of the determinants of union bargaining power, based in considerable part on Marshall's theory of joint demand. From this analysis Professor Friedman derives in substance the following conclusions: I. Generally speaking, it can be predicted that craft unions are strong while industrial unions are weak, partly because, in the long run, the elasticity of demand for the labor of members of industrial unions can be expected to be much greater than the elasticity of demand for the labor of the crafts. This is significant for the empirical problem of assessing the magnitude of the impact of unionism upon the structure and level of wages, because the membership of the craft unions constitutes only a small percentage of the total labor force. 2. To be effective in raising and maintaining wage rates above the levels which would have prevailed in their absence, unions be able to restrict the supply of workers or they must be able to exercise control over employers they be able to prevent existing employers from undercutting the union wage rate, as well as the entry of new employers who would do so. 3. Wage increases in unionized sectors of the economy imply wage reductions elsewhere (page 2I6). This statement follows from Friedman's interpretation of the nature of the impact of unionism on the supply of labor. 4. In inflationary periods unions probably prevent wages from rising as rapidly as they otherwise would (pages 226-27). This statement follows from an argument which is not directly related to Friedman's analyses of demand and supply, although it rests upon the conclusions derived therefrom. Friedman thus holds that craft unions are significantly stronger than industrial unions, that the over-all impact of unionism upon the structure of wages is weak (relatively few workers are organized in craft unions pages 205206), and that, by implication, the impact of unionism upon the general level of money wages is even weaker. Friedman sought to test his conclusions by comparing certain changes in wages and prices during three wartime inflationary periods (pages 2I7-2I), and he found that the relative increase in money wages (and in prices) in the World War I period, when union membership reached a maximum of about one-eighth of the work force, was virtually identical with the relative increase in money wages (and in prices) in the World War II period, when union membership constituted about one-quarter of the work force (pages